Handelskapital und Handelskapitalismus: Zur Theorie des frühen europäischen Kapitalismus - Kriedte, Peter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
Towards a theory of early European capitalism The starting point of the paper is Marx's theory of merchant capital. In contrast to Fernand Brandei the author argues that the early European capitalism was distinctive from its later forms. Five elements of a theory of merchant capitalism are discussed: the hierarchy of the economic spheres, the relation to the sphere of production, merchant capital and precapitalist modes of production, merchant and financial capital, protection und protection costs.